ANALISIS DAYA TAHAN AEROBIK (VO2MAX) MAHASISWA PENJASKESREK FKIP UNIVESITAS ABULYATAMA YANG MENGIKUTI MATAKULIAH ATLETIK - Purnomo, Adi; Juwanda, Rawi; Musran, Musran; Syahrinursaifi, Syahrinursaifi (Jurnal Dedikasi Pendidikan, 2024)
The purpose of this study was to analyze aerobic endurance (VO2Max) in Health and Recreation Physical Education students, Faculty of Teacher Training and Education, Abulyatama University who took the Athletics Course. This research is a type of descriptive research with a quantitative approach. The population and research sample totaled 35 Students of Physical Education, Health and Recreation, Faculty of Teacher Training and Education, Abulyatama University, Class of 2022. The data collection for this study was through a 15-minute running test and measurement. The results showed that the average analysis of aerobic endurance (VO2Max) of Physical Education Health and Recreation students, Faculty of Teacher Training and Education, Abulyatama University who took part in the Athletics Course was 33.79 (very poor category), with the following details: (1) as many as 2 students (5.71%) are in the medium category, (2) as many as 33 students (94.29%) were in the very poor category. The conclusion of this research is that the aerobic endurance (VO2Max) of Physical Education Health and Recreation students at the Faculty of Teacher Training and Education, Abulyatama University who take the Athletics Course is very poor